Optimizing the Sum of Linear Absolute Value Functions on An Interval - Khashshan, M. M. (Journal of Informatics and Mathematical Sciences, 2012)
In this paper we give a new result for solving the problem of optimizing the sum of absolute values in the form $|x-a_r|$ over any interval.